2017
DOI: 10.1103/physrevphyseducres.13.020116
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of socially mediated metacognition during collaborative troubleshooting of electric circuits

Abstract: Developing students' ability to troubleshoot is an important learning outcome for many undergraduate physics lab courses, especially electronics courses. In other work, metacognition has been identified as an important feature of troubleshooting. However, that work has focused primarily on individual students' metacognitive processes or troubleshooting abilities. In contrast, electronics courses often require students to work in pairs, and hence students' in-class experiences likely have significant social dim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 45 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…This is consistent with research that has shown that collaboration and metacognition are mutually related (Frith, 2012). The development of individual metacognitive skills improves the nature of the collaboration as individuals become more aware and reflective, and at the same time, collaboration benefits individuals' MA by helping them reflect on their own actions (Goos et al, 2002; Van De Bogart et al, 2017). In fact, a growing body of literature has begun to establish the important connection between social learning experiences and the development of individual MA (Goos et al, 2002; Hogan & Tudge, 1999; Järvelä et al, 2015; Liskala et al, 2004; Zion et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with research that has shown that collaboration and metacognition are mutually related (Frith, 2012). The development of individual metacognitive skills improves the nature of the collaboration as individuals become more aware and reflective, and at the same time, collaboration benefits individuals' MA by helping them reflect on their own actions (Goos et al, 2002; Van De Bogart et al, 2017). In fact, a growing body of literature has begun to establish the important connection between social learning experiences and the development of individual MA (Goos et al, 2002; Hogan & Tudge, 1999; Järvelä et al, 2015; Liskala et al, 2004; Zion et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…, 2002 ). Students also use social metacognition when they assess, modify, and enact one another’s strategies for solving problems ( Van De Bogart et al. , 2017 ).…”
Section: Promoting Social Metacognition During Group Workmentioning
confidence: 99%
“…According to a cognitive model of troubleshooting by Jonnasen and Hung, the process involves constructing a problem space, identifying faulty symptoms, diagnosing faults, generating and verifying solutions, and remembering the experience [10]. Self-regulation, which refers to "self-generated thoughts, feelings and actions that are planned and cyclically adapted to the attainment of personal goals" [11], therefore plays a key role in troubleshooting [12].…”
Section: Study Motivationmentioning
confidence: 99%